Morse Fall Scale As Clinical Predictor Of 3-Month Neurologic Function Recovery On Ischemic Stroke Patients: A Prospective Cohort Study - Triono Agung Sakti; Baarid Luqman Hamidi; Hanindia Riani Prabaningtyas (Department of Neurology Faculty of Medicine Universitas Sebelas Maret, 2023)
Background: Stroke is a leading cause of death in developing countries. The Morse Fall Scale (MFS)'s use in predicting stroke clinical outcomes has not been extensively studied. This study aims to assess MFS's ability to predict neurological recovery in acute ischemic stroke patients within 3 months using the National Institutes of Health Stroke Scale (NIHSS). Methods: This prospective cohort study enrolled all individuals with acute ischemic stroke between September and November 2021. Patients' baseline data included their MFS and NIHSS scores, as well as their age, gender, weight, stroke location, and comorbidities. The NIHSS score was reassessed three months later. To identify NIHSS predictors, all baseline data will be analyzed. SPSS 22 was used to analyze the data. The local ethics committee approved the study. Results: Of the 164 patients who met the criteria, only 105 (mean age 59.09 [±11.65], male [58.1%], anterior location [88.6%]) reached the study end point. The average NIHSS score decreased from 9.14 (±1.70) to 6.27 (±1.92). Multiple linear regression showed only the MFS score (p = 0.000) accurately predicted the NIHSS by 0.059 (95% CI: 0.032–0.085, p = 0.000) at the study's conclusion. Discussion: Our investigation revealed that the baseline MFS score accurately predicted neurological improvement in patients who had suffered an ischemic stroke over a three-month period. It is considered that the greater risk of falling results in a delay in the patient's rehabilitation. Investigation with larger sample sizes and longer monitoring intervals are required to corroborate our findings.